Health professionals and trust : the cure for healthcare law and policy - Henaghan, Mark. (New York : Routledge-Cavendish, 2011)
'Over the past twenty years there has been a shift in medical law and practise to increasingly distrust the judgement of health professionals. An increasing number of codes of conduct, disciplinary bodies, ethics committees and bureaucratic policies now prescribe how health professional and health researchers should act and relate to their patients. The result of this, Mark Henaghan argues, has been to undermine trust and professional judgement in health professionals, while simultaneously failing to trust the patient to make decisions about their care. This book will look at the issue of health professionals and trust comparatively in a number of countries including the USA, Canada, Australia, New Zealand and the UK. The book will show by historical analysis of legislation, case law, disciplinary proceedings reports, articles in medical and law journals and protocols produced by management teams in hospitals, how the shift from trust to lack of trust has happened. Drawing comparisons between situations where trust is respected such as in emergency situations, and where it is not for example routine decisions such as obtaining consent for an anaesthetic procedure, the book shows how this erosion of trust has the potential to dehumanise the special nature of the relationship between healthcare professionals and patients. The effect of this is that the practice of health care is turned into a mechanistic enterprise controlled by'management processes' rather than governed by trust and individual care and judgement. This book will be an invaluable resource for students and scholars of medical law and medical sociology, public policy-makers and a range of associated professionals, from health service managers to medical science and clinical researchers'--
'An ever increasing number of codes of conduct, disciplinary bodies, ethics committees and bureaucratic policies now prescribe how health professionals and health researchers relate to their patients. In this book, Mark Henaghan argues that the result of this trend towards heightened regulation has been to undermine the traditional dynamic of trust in health professionals and to diminish reliance upon their professional judgement, whilst simultaneously failing to trust patients to make decisions about their own care. This book examines the issue of health professionals and trust comparatively in a number of countries including the USA, Canada, Australia, New Zealand and the UK. The book draws upon historical analysis of legislation, case law, disciplinary proceedings reports, articles in medical and law journals and protocols produced by management teams in hospitals, to illustrate the ways in which there has been a discernable shift away from trust in healthcare professionals. Henaghan argues that this erosion of trust has the potential to dehumanise the unique relationship that has traditionally existed between healthcare professionals and their patients, thereby running the risk of turning healthcare into a mechanistic enterprise controlled by a'management processes' rather than a humanistic relationship governed by trust and judgement. This book is an invaluable resource for students and scholars of medical law and medical sociology, public policy-makers and a range of associated professionals, from health service managers to medical science and clinical researchers'--
Includes bibliographical references and index.
Keywords: Medical care -- Law and legislation; Medical personnel and patient; Communication in medicine; Medical personnel -- Discipline; Patients -- Legal status, laws, etc; Medical ethics